HABITAT PREFERENCE OF CHILOPODA AND DIPLOPODA OF THE FAUNA OF THE CENTRAL CISCAUCASIA - Roman Vladimirovich Zuev; Sergey Ivanovich Sigida (Наука. Инновации. Технологии)
Central Ciscaucasia is experiencing significant anthropogenic loads from the XIX century. About 90% of the territory of the Stavropol Territory is used for agricultural needs, which has a significant impact on the inhabitants of the soil. An important component of the soil fauna are representatives by the Diplopoda and Chilopoda. In the given work the analysis of habitat preference of these arthropods to native and anthropogenic biotopes is analyzed to assess the impact of human activity on members of these groups. The material for the present work was collected from 2004-2017 in the native and anthropogenic biocenoses of the Central Ciscaucasia. Specimens were taken either by hand or using soil sampling. In total, more than 3 thousand Diplopoda and Chilopoda were collected and processed. A total of 55 species were identified in the study area. The largest species diversity in the natural gully and floodplain forests (45 species). The fauna of the steppes is less rich (25). In this case, a decrease in species diversity is observed in various steppe biotopes with a decrease in humidity (up to 5 species in sagebrush steppes). The study area has undergone a significant anthropogenic transformation. Only 6 species of millipedes were found on the ield. Field-protecting forest belts are the richest species between anthropogenic biocenosis. They served as a refugium for the natural steppe fauna and "corridors" for spreading of some forest species. In the gardens there are 9 species of Chilopoda and 4 - Diplopoda. The gardens and urbocenosis characterized by the presence of anthropochoric species. The greatest variety of Diplopoda and Chilopoda (82% of species) is observed in forest biotopes, which occupy about 1.5% of the area under study. Reduction of species composition of the Myriapoda in the steppes is connected with a decreasion in soil moisture. This trend is also observed among the steppes of various types: 25 species in mixed-grass, 12 species in fescue feather grass and 5 in sagebrush steppes. In sagebrush steppes millipedes are completely absent. Scolopendra cingulata is the only species conined to steppe biotopes only. Anthropogenic transformation of natural biotopes adversely affects the diversity of millipedes. The greatest damage is caused by plowing of the land: in the fields there are only two types of diplopods and 4 - chilopods, 13 species of millipedes are found in gardens, 20 in urban areas. The creation of ield-protecting forest belts has played a certain positive role. They contribute to the preservation of elements of the native fauna of the Central Ciscaucasia.